Efektivitas Kebijakan Fiskal Pemerintah dalam Mendorong Pertumbuhan Ekonomi Ditinjau dari Teori Keynesian - Ambarita, Charles Fransiscus; Siregar, Ade Rahma Sintiya (SAFE-Network, 2025)
This article discusses the effectiveness of government fiscal policy in promoting Indonesia's economic growth using the Keynesian theory perspective. The research was conducted using a quantitative descriptive approach with secondary data from the Central Statistics Agency (BPS) for the period 2019-2023, covering macroeconomic indicators such as household consumption, investment, government spending, exports and imports, and Gross Domestic Product (GDP). The results show that active government intervention through increased state spending, social assistance programs, subsidies, and fiscal incentives can increase aggregate demand, expand employment opportunities, and strengthen people's purchasing power. Infrastructure development and international trade support have also been shown to contribute to expanding national production capacity and increasing global competitiveness. These findings confirm the relevance of Keynesian theory in the context of the Indonesian economy, where expansionary fiscal policy is not only capable of maintaining stability but also promoting sustainable economic growth. However, the implementation of such policies needs to be more focused on sustainability and social equity so that development outcomes can be more inclusive and just.